PENERAPAN BUDAYA KERJA DAN KONTROL MANAJEMEN DALAM UPAYA MENINGKATKAN MOTIVASI KERJA - Anggraeni Anggraeni (Universitas Pamulang, 2021)
Work motivation is a psychological factor for performance, achievement, and work productivity. That is, morale is a variable that determines the quality of work implementation, the extent to which employees have a high desire and a feeling of optimism in achieving the goals that have been set. This study aims to reveal the possibility of work motivation in terms of culture and management control aspects. The research method uses causal association, with a total of 120 respondents. The analysis technique uses a linear regression statistical approach. The results showed that work culture can explain work motivation with a regression estimate of 0.701 and management control has a role of 0.718. This finding, in comparison, states that employees have a tendency to be very enthusiastic if the company implements a good control function. This can happen because control affects employees' feelings of discomfort at work, so that the opportunities for laziness and or lack of responsibility are reduced. In addition, the implementation of management control gives birth to the assumption that employees feel cared for, so they are enthusiastic about carrying out their duties.Keywords: Work Culture, Management Control, Work Motivation